LEGAL CERTAINTY REGARDING THE IMPLEMENTATION OF GOVERNMENT REGULATION NUMBER 77 OF 2019 CONCERNING THE PREVENTION OF TERRORISM CRIMINAL ACTS AND PROTECTION OF INVESTIGATORS, PUBLIC PROSECUTORS, JUDGES AND CORRECTION OFFICERS - Sidhiwaskita, I Gusti Agung Bagas; Sujono (JILPR Journal Indonesia Law and Policy Review, 2025)
Terrorism poses a threat and intimidation to national security, as acts of terrorism constitute actions that create the greatest danger to human rights. To anticipate the issue of terrorism crimes, Indonesia, as a rule of law state, has the obligation and responsibility to live safely, peacefully, and prosperously, as outlined in the constitutional mandate of the 1945 Constitution of the Republic of Indonesia. Therefore, further research will be conducted on the legal certainty of the implementation of Government Regulation Number 77 of 2019 concerning the prevention of terrorism crimes and the protection of investigators, public prosecutors, judges, and correctional officers, and the roles of the National Counterterrorism Agency (BNPT) and Detachment 88 in the prevention and eradication of terrorism crimes. The research method used is normative juridical. The research findings indicate that the implementation of Government Regulation 77/2019 as the execution of Law 5/2018 provides legal certainty for investigators, public prosecutors, judges, and correctional officers in combating and preventing terrorism crimes, as Government Regulation 77/2019 serves as the basis for all actions in counterterrorism. BNPT plays a role in prevention, protection, and deradicalization efforts, as well as in enforcement and capacity building, including international cooperation in addressing terrorism challenges. Detachment 88's role is to investigate reports of terrorist activities, arrest individuals or groups confirmed to be members of terrorist networks that could endanger the integrity and security of the Republic of Indonesia. The research results suggest that improvements should be made by legalizing material criminal penalties that include aggravated criminal threats in cases of attacks against law enforcement officers handling terrorism crimes, and the government should establish a new Special Law concerning the Protection and Counterterrorism of investigators, public prosecutors, judges, and correctional officers in Laws, Regulations, Government Regulations, and Regulations of the Ministry of Law and Human Rights.